A nano calcium carbonate modification method and its application in PE blown film
The integration of modified calcium carbonate nanoparticles into PE membranes addresses the thermal and mechanical limitations of conventional PE membranes, enhancing their performance and expanding their application scope in high-temperature, high-humidity environments.
Patent Information
- Application Number
- CN202310276577.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-03-21
AI Technical Summary
Conventional polyethylene (PE) membranes have limitations in terms of thermal stability and mechanical performance, particularly at high temperatures and in humid environments, leading to reduced lifespan and restricted application domains.
A method for modifying calcium carbonate nanoparticles by a multi-step process involving the use of deionized water, oxides, shell sugars, citric acid, carbon dioxide, ethylene glycol, and specific surfactants to create a stable dispersion, which is then incorporated into the PE membrane, enhancing its mechanical and thermal properties.
The modified nanoparticles significantly improve the mechanical and high-temperature, high-humidity performance of PE membranes, extending their usage and applicability in more demanding conditions.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PE materials, and in particular to a nano calcium carbonate modification method and application thereof in PE film blowing. Background Art
[0002] Calcium carbonate, as a commonly used inorganic powder filler material for plastics, can reduce product production costs, improve the dimensional stability, heat resistance, and tensile strength of plastic products, play a role in light dispersion and extinction, and improve the processing and forming properties of plastics. It has many advantages that other powder materials do not have, so it is widely used in the plastics industry. Polyethylene (PE for short) is a thermoplastic resin obtained by polymerization of ethylene. In industry, it also includes copolymers of ethylene and a small amount of α-olefins. Polyethylene is odorless, non-toxic, feels like wax, has excellent low-temperature resistance (the lowest operating temperature can reach -100℃~-70℃), good chemical stability, and can withstand the corrosion of most acids and alkalis (not resistant to oxidizing acids). It is insoluble in general solvents at room temperature, has low water absorption, and excellent electrical insulation. Therefore, it is currently widely used in all walks of life. Polyethylene film is the most widely used polymer material in the world today. PE film uses special polyethylene (PE) plastic film as the base material and is divided into high-density polyethylene protective film, medium-density polyethylene, and low-density polyethylene according to different densities. Polyethylene film has now been widely used in the pharmaceutical, chemical, food, electronics, printing and other industries. However, due to some characteristics of the properties of polyethylene itself, polyethylene film also has some shortcomings in application. For example, the temperature resistance of polyethylene is not high. The polyethylene film currently used on the market generally does not exceed 100°C. Therefore, polyethylene film will be restricted in some special fields. At the same time, in situations with high stress, polyethylene film is prone to deformation and cracking, thus affecting its service life. These aspects have greatly limited the application of polyethylene film. Summary of the invention
[0003] To this end, the present invention provides a method for modifying nano calcium carbonate, comprising the following steps:
[0004] (1) keeping the deionized water bath at a constant temperature of 80±5°C, then adding calcium oxide powder to the deionized water, stirring for more than 2 hours after the addition is completed, and then standing at 80±5°C for more than 15 hours to obtain a suspension of calcium hydroxide;
[0005] (2) preparing a composite aqueous solution of chitosan oligosaccharide and sodium citrate, and keeping the calcium hydroxide suspension in a water bath at a constant temperature of 90±5° C.; stirring the calcium hydroxide suspension kept at 90±5° C., and then adding the composite aqueous solution of chitosan oligosaccharide and sodium citrate to the calcium hydroxide suspension under stirring, while introducing carbon dioxide gas, and after aeration reaction for more than 4 hours, stopping aeration, air-cooling the suspension to room temperature, separating the solid and liquid, washing the solid phase with deionized water, and drying to obtain calcium carbonate powder;
[0006] (3) dispersing the calcium carbonate powder in an ethanol solution of polyethylene glycol to obtain a dispersion, dropping triethylamine into the dispersion, then thermostating the dispersion in a water bath to 70±5° C., stirring the dispersion after thermostatting, adding tridecafluorooctyl triethoxysilane to the dispersion during stirring, continuing to thermostat stir for more than 3 hours after the addition is completed, then stopping stirring, air cooling to room temperature, separating the solid and liquid, and drying the solid phase to obtain a solid phase A;
[0007] (4) dispersing the solid phase A in ethanol to form an ethanol dispersion, and the ethanol dispersion is kept at a constant temperature of 65±5° C. in a water bath, condensed and refluxed, and chlorogenic acid and dopamine hydrochloride are added to the ethanol dispersion after the constant temperature is maintained. After the addition is completed, the mixture is stirred at a constant temperature for more than 6 hours, and then air-cooled to room temperature, the solid-liquid separation is performed, and the solid phase is dried to obtain the modified nano-calcium carbonate.
[0008] Furthermore, the mass ratio of calcium oxide powder added to deionized water is calcium oxide powder: deionized water = 1:5-6.
[0009] Furthermore, in the composite aqueous solution of chitosan oligosaccharide and sodium citrate, the mass percentage of chitosan oligosaccharide is 3% to 5%, the mass percentage of sodium citrate is 0.2% to 0.3%, and the solvent is water; the composite aqueous solution of chitosan oligosaccharide and sodium citrate is added to the suspension of calcium hydroxide in a volume ratio of calcium hydroxide suspension: composite aqueous solution of chitosan oligosaccharide and sodium citrate = 10:2 to 4.
[0010] Furthermore, the introduction speed of the carbon dioxide gas is 0.5 m / s. 3 / h.
[0011] Furthermore, in the polyethylene glycol ethanol solution, the concentration of polyethylene glycol is 10-15 g / L, and the solid-liquid mass ratio of the calcium carbonate powder dispersed in the polyethylene glycol ethanol solution is solid / liquid=1:30.
[0012] Furthermore, the mass of the triethylamine added is 3 to 5 times the mass of the calcium carbonate powder in the dispersion; the mass of the tridecafluorooctyltriethoxysilane added is 1 to 2 times the mass of the calcium carbonate powder in the dispersion.
[0013] Furthermore, the solid-liquid mass ratio of the solid phase A dispersed in ethanol is solid / liquid=1:20; the mass ratio of the added mass of the chlorogenic acid and dopamine hydrochloride to the solid phase A is chlorogenic acid: dopamine hydrochloride: solid phase A=1-2:0.3-0.6:1.
[0014] The invention also discloses a PE film, wherein the PE film contains the modified nano calcium carbonate.
[0015] The beneficial effect of the present invention is that after the modified nano calcium carbonate prepared by the method of the present invention is added to a PE film, the mechanical properties and high temperature and high humidity resistance of the PE film can be significantly improved, the service life of the PE film is increased, and at the same time, the PE film can be used for a long time in a high temperature and high humidity environment, thereby broadening the use field and conditions of the PE film. DETAILED DESCRIPTION
[0016] The present invention will be further described below in conjunction with the embodiments.
[0017] Example 1
[0018] A method for modifying nano calcium carbonate comprises the following steps:
[0019] (1) keeping the deionized water bath at a constant temperature of 80±5°C, then adding calcium oxide powder to the deionized water, the mass ratio of calcium oxide powder to deionized water being 1:5; stirring at 100 r / min for 2 h after the addition, then standing at 80±5°C for 15 h to obtain a suspension of calcium hydroxide;
[0020] (2) preparing a composite aqueous solution of chitosan oligosaccharide and sodium citrate, wherein the mass percentage of chitosan oligosaccharide and the mass percentage of sodium citrate are 3%, the mass percentage of sodium citrate is 0.2%, and the solvent is water; the calcium hydroxide suspension is kept at a constant temperature of 90±5°C in a water bath; the calcium hydroxide suspension is stirred at 60r / min at 90±5°C, and then the composite aqueous solution of chitosan oligosaccharide and sodium citrate is added to the calcium hydroxide suspension under stirring, and the volume ratio of the composite aqueous solution of chitosan oligosaccharide and sodium citrate added to the calcium hydroxide suspension is 10:2; and carbon dioxide gas is introduced at the same time, and the introduction speed of carbon dioxide gas is 0.5m / min. 3 / h, after aeration reaction for 4h, aeration was stopped, the suspension was air-cooled to room temperature, the solid-liquid was separated, the solid phase was washed with deionized water, and dried to obtain calcium carbonate powder;
[0021] (3) dispersing the calcium carbonate powder in an ethanol solution of polyethylene glycol (PEG-1000) to obtain a dispersion, wherein the concentration of polyethylene glycol in the ethanol solution is 10 g / L, and the solid-liquid mass ratio of the calcium carbonate powder dispersed in the ethanol solution of polyethylene glycol is solid / liquid=1:30; dripping triethylamine into the dispersion, then thermostating the dispersion to 70±5° C. in a water bath, stirring the dispersion at 60 r / min after thermostatting, adding tridecafluorooctyl triethoxysilane to the dispersion during stirring, and continuing to stir at a constant temperature of 60 r / min for 3 hours after the addition is completed, wherein the mass of the triethylamine added is 3 times the mass of the calcium carbonate powder in the dispersion; the mass of the tridecafluorooctyl triethoxysilane added is 2 times the mass of the calcium carbonate powder in the dispersion; then stopping stirring, air cooling to room temperature, solid-liquid separation, and solid phase drying to obtain solid phase A;
[0022] (4) dispersing the solid phase A in ethanol to form an ethanol dispersion, wherein the solid-liquid mass ratio of the solid phase A dispersed in ethanol is solid / liquid=1:20; the ethanol dispersion is kept at a constant temperature of 65±5°C in a water bath, condensed and refluxed, and after the constant temperature is maintained, chlorogenic acid and dopamine hydrochloride are added to the ethanol dispersion, wherein the mass ratio of the added chlorogenic acid and dopamine hydrochloride to the solid phase A is chlorogenic acid: dopamine hydrochloride: solid phase A=1:0.3:1; after the addition is completed, stirring is carried out at a constant temperature of 60r / min for 6h, and then air-cooled to room temperature, the solid-liquid separation is carried out, and the solid phase is dried to obtain the modified nano-calcium carbonate.
[0023] Example 2
[0024] A method for modifying nano calcium carbonate comprises the following steps:
[0025] (1) keeping the deionized water bath at a constant temperature of 80±5°C, then adding calcium oxide powder to the deionized water, the mass ratio of calcium oxide powder to deionized water being 1:5; stirring at 100 r / min for 2 h after the addition, then standing at 80±5°C for 15 h to obtain a suspension of calcium hydroxide;
[0026] (2) preparing a composite aqueous solution of chitosan oligosaccharide and sodium citrate, wherein the mass percentage of chitosan oligosaccharide and the mass percentage of sodium citrate is 4%, the mass percentage of sodium citrate is 0.2%, and the solvent is water; the calcium hydroxide suspension is kept at a constant temperature of 90±5°C in a water bath; the calcium hydroxide suspension kept at 90±5°C is stirred at 60 r / min, and then the composite aqueous solution of chitosan oligosaccharide and sodium citrate is added to the calcium hydroxide suspension under stirring, and the volume ratio of the composite aqueous solution of chitosan oligosaccharide and sodium citrate added to the calcium hydroxide suspension is 10:3; and carbon dioxide gas is introduced at a speed of 0.5 m / s. 3 / h, after aeration reaction for 4h, aeration was stopped, the suspension was air-cooled to room temperature, the solid-liquid was separated, the solid phase was washed with deionized water, and dried to obtain calcium carbonate powder;
[0027] (3) dispersing the calcium carbonate powder in an ethanol solution of polyethylene glycol (PEG-1000) to obtain a dispersion, wherein the concentration of polyethylene glycol in the ethanol solution is 12 g / L, and the solid-liquid mass ratio of the calcium carbonate powder dispersed in the ethanol solution of polyethylene glycol is solid / liquid=1:30; dripping triethylamine into the dispersion, then thermostating the dispersion to 70±5° C. in a water bath, stirring the dispersion at 60 r / min after thermostatting, adding tridecafluorooctyl triethoxysilane to the dispersion during stirring, and continuing to stir at a constant temperature of 60 r / min for 3 h after the addition is completed, wherein the mass of the triethylamine added is 4 times the mass of the calcium carbonate powder in the dispersion; the mass of the tridecafluorooctyl triethoxysilane added is 2 times the mass of the calcium carbonate powder in the dispersion; then stopping stirring, air cooling to room temperature, solid-liquid separation, and solid phase drying to obtain solid phase A;
[0028] (4) dispersing the solid phase A in ethanol to form an ethanol dispersion, wherein the solid-liquid mass ratio of the solid phase A dispersed in ethanol is solid / liquid = 1:20; the ethanol dispersion is kept at a constant temperature of 65±5°C in a water bath, condensed and refluxed, and after the constant temperature is maintained, chlorogenic acid and dopamine hydrochloride are added to the ethanol dispersion, wherein the mass ratio of the added chlorogenic acid and dopamine hydrochloride to the solid phase A is chlorogenic acid: dopamine hydrochloride: solid phase A = 1:0.4:1; after the addition is completed, stirring is carried out at a constant temperature of 60r / min for 6h, and then air-cooling is carried out to room temperature, solid-liquid separation is carried out, and the solid phase is dried to obtain the modified nano-calcium carbonate.
[0029] Example 3
[0030] A method for modifying nano calcium carbonate comprises the following steps:
[0031] (1) keeping the deionized water bath at a constant temperature of 80±5°C, then adding calcium oxide powder to the deionized water, the mass ratio of calcium oxide powder to deionized water being 1:6; stirring at 100 r / min for 2 h after the addition, then standing at 80±5°C for 15 h to obtain a suspension of calcium hydroxide;
[0032] (2) preparing a composite aqueous solution of chitosan oligosaccharide and sodium citrate, wherein the mass percentage of chitosan oligosaccharide and the mass percentage of sodium citrate is 4%, the mass percentage of sodium citrate is 0.3%, and the solvent is water; the calcium hydroxide suspension is kept at a constant temperature of 90±5°C in a water bath; the calcium hydroxide suspension is stirred at 60r / min at 90±5°C, and then the composite aqueous solution of chitosan oligosaccharide and sodium citrate is added to the calcium hydroxide suspension under stirring, and the volume ratio of the composite aqueous solution of chitosan oligosaccharide and sodium citrate added to the calcium hydroxide suspension is 10:3; and carbon dioxide gas is introduced at a speed of 0.5m / s. 3 / h, after aeration reaction for 4h, aeration was stopped, the suspension was air-cooled to room temperature, the solid-liquid was separated, the solid phase was washed with deionized water, and dried to obtain calcium carbonate powder;
[0033] (3) dispersing the calcium carbonate powder in an ethanol solution of polyethylene glycol (PEG-1000) to obtain a dispersion, wherein the concentration of polyethylene glycol in the ethanol solution is 14 g / L, and the solid-liquid mass ratio of the calcium carbonate powder dispersed in the ethanol solution of polyethylene glycol is solid / liquid=1:30; dripping triethylamine into the dispersion, then thermostating the dispersion to 70±5° C. in a water bath, stirring the dispersion at 60 r / min after thermostatting, adding tridecafluorooctyl triethoxysilane to the dispersion during stirring, and continuing to stir at a constant temperature of 60 r / min for 3 hours after the addition is completed, wherein the mass of the triethylamine added is 4 times the mass of the calcium carbonate powder in the dispersion; the mass of the tridecafluorooctyl triethoxysilane added is 2 times the mass of the calcium carbonate powder in the dispersion; then stopping stirring, air cooling to room temperature, solid-liquid separation, and solid phase drying to obtain solid phase A;
[0034] (4) dispersing the solid phase A in ethanol to form an ethanol dispersion, wherein the solid-liquid mass ratio of the solid phase A dispersed in ethanol is solid / liquid = 1:20; the ethanol dispersion is kept at a constant temperature of 65±5°C in a water bath, condensed and refluxed, and after the constant temperature is maintained, chlorogenic acid and dopamine hydrochloride are added to the ethanol dispersion, wherein the mass ratio of the added chlorogenic acid and dopamine hydrochloride to the solid phase A is chlorogenic acid: dopamine hydrochloride: solid phase A = 2:0.5:1; after the addition is completed, stirring is carried out at a constant temperature of 60r / min for 6h, and then air-cooled to room temperature, the solid-liquid separation is carried out, and the solid phase is dried to obtain the modified nano-calcium carbonate.
[0035] Example 4
[0036] A method for modifying nano calcium carbonate comprises the following steps:
[0037] (1) keeping the deionized water bath at a constant temperature of 80±5°C, then adding calcium oxide powder to the deionized water, the mass ratio of calcium oxide powder to deionized water being 1:6; stirring at 100 r / min for 2 h after the addition, then standing at 80±5°C for 15 h to obtain a suspension of calcium hydroxide;
[0038] (2) preparing a composite aqueous solution of chitosan oligosaccharide and sodium citrate, wherein the mass percentage of chitosan oligosaccharide and the mass percentage of sodium citrate are 5%, the mass percentage of sodium citrate is 0.3%, and the solvent is water; the calcium hydroxide suspension is kept at a constant temperature of 90±5°C in a water bath; the calcium hydroxide suspension is stirred at 60r / min at 90±5°C, and then the composite aqueous solution of chitosan oligosaccharide and sodium citrate is added to the calcium hydroxide suspension under stirring, and the volume ratio of the composite aqueous solution of chitosan oligosaccharide and sodium citrate added to the calcium hydroxide suspension is 10:4; and carbon dioxide gas is introduced at the same time, and the introduction speed of carbon dioxide gas is 0.5m / min. 3 / h, after aeration reaction for 4h, aeration was stopped, the suspension was air-cooled to room temperature, the solid-liquid was separated, the solid phase was washed with deionized water, and dried to obtain calcium carbonate powder;
[0039] (3) dispersing the calcium carbonate powder in an ethanol solution of polyethylene glycol (PEG-1000) to obtain a dispersion, wherein the concentration of polyethylene glycol in the ethanol solution is 15 g / L, and the solid-liquid mass ratio of the calcium carbonate powder dispersed in the ethanol solution of polyethylene glycol is solid / liquid=1:30; dripping triethylamine into the dispersion, then thermostating the dispersion to 70±5° C. in a water bath, stirring the dispersion at 60 r / min after thermostatting, adding tridecafluorooctyl triethoxysilane to the dispersion during stirring, and continuing to stir at a constant temperature of 60 r / min for 3 hours after the addition is completed, wherein the mass of the triethylamine added is 5 times the mass of the calcium carbonate powder in the dispersion; the mass of the tridecafluorooctyl triethoxysilane added is 2 times the mass of the calcium carbonate powder in the dispersion; then stopping stirring, air cooling to room temperature, solid-liquid separation, and solid phase drying to obtain solid phase A;
[0040] (4) dispersing the solid phase A in ethanol to form an ethanol dispersion, wherein the solid-liquid mass ratio of the solid phase A dispersed in ethanol is solid / liquid = 1:20; the ethanol dispersion is kept at a constant temperature of 65±5°C in a water bath, condensed and refluxed, and after the constant temperature is maintained, chlorogenic acid and dopamine hydrochloride are added to the ethanol dispersion, wherein the mass ratio of the added chlorogenic acid and dopamine hydrochloride to the solid phase A is chlorogenic acid: dopamine hydrochloride: solid phase A = 2:0.6:1; after the addition is completed, stirring is carried out at a constant temperature of 60r / min for 6h, and then air-cooling is carried out to room temperature, solid-liquid separation is carried out, and the solid phase is dried to obtain the modified nano-calcium carbonate.
[0041] Comparative Example 1
[0042] A comparative calcium carbonate modification method comprises the following steps:
[0043] (1) keeping the deionized water bath at a constant temperature of 80±5°C, then adding calcium oxide powder to the deionized water, the mass ratio of calcium oxide powder to deionized water being 1:5; stirring at 100 r / min for 2 h after the addition, then standing at 80±5°C for 15 h to obtain a suspension of calcium hydroxide;
[0044] (2) preparing an aqueous solution of sodium citrate, wherein the mass percentage of sodium citrate in the aqueous solution of sodium citrate is 0.2%, and the solvent is water; the calcium hydroxide suspension is kept at a constant temperature of 90±5° C. in a water bath; stirring the calcium hydroxide suspension kept at 90±5° C. at 60 r / min, and then adding the aqueous solution of sodium citrate to the calcium hydroxide suspension under stirring, wherein the volume ratio of the aqueous solution of sodium citrate to the calcium hydroxide suspension is 10:3; and simultaneously introducing carbon dioxide gas at a rate of 0.5 m / s. 3 / h, after aeration reaction for 4h, aeration was stopped, the suspension was air-cooled to room temperature, the solid-liquid was separated, the solid phase was washed with deionized water, and dried to obtain calcium carbonate powder;
[0045] (3) dispersing the calcium carbonate powder in an ethanol solution of polyethylene glycol (PEG-1000) to obtain a dispersion, wherein the concentration of polyethylene glycol in the ethanol solution is 12 g / L, and the solid-liquid mass ratio of the calcium carbonate powder dispersed in the ethanol solution of polyethylene glycol is solid / liquid=1:30; dripping triethylamine into the dispersion, then thermostating the dispersion to 70±5° C. in a water bath, stirring the dispersion at 60 r / min after thermostatting, adding tridecafluorooctyl triethoxysilane to the dispersion during stirring, and continuing to stir at a constant temperature of 60 r / min for 3 h after the addition is completed, wherein the mass of the triethylamine added is 4 times the mass of the calcium carbonate powder in the dispersion; the mass of the tridecafluorooctyl triethoxysilane added is 2 times the mass of the calcium carbonate powder in the dispersion; then stopping stirring, air cooling to room temperature, solid-liquid separation, and solid phase drying to obtain solid phase A;
[0046] (4) The solid phase A is dispersed in ethanol to form an ethanol dispersion, wherein the solid-liquid mass ratio of the solid phase A dispersed in ethanol is solid / liquid = 1:20; the ethanol dispersion is kept at a constant temperature of 65±5°C in a water bath, condensed and refluxed, and after the constant temperature, chlorogenic acid and dopamine hydrochloride are added to the ethanol dispersion, wherein the mass ratio of the added chlorogenic acid and dopamine hydrochloride to the solid phase A is chlorogenic acid: dopamine hydrochloride: solid phase A = 1:0.4:1; after the addition is completed, the mixture is stirred at a constant temperature of 60r / min for 6h, then air-cooled to room temperature, the solid-liquid is separated, and the solid phase is dried to obtain the modified nano-calcium carbonate of this comparative example.
[0047] Comparative Example 2
[0048] A comparative calcium carbonate modification method comprises the following steps:
[0049] (1) keeping the deionized water bath at a constant temperature of 80±5°C, then adding calcium oxide powder to the deionized water, the mass ratio of calcium oxide powder to deionized water being 1:5; stirring at 100 r / min for 2 h after the addition, then standing at 80±5°C for 15 h to obtain a suspension of calcium hydroxide;
[0050] (2) preparing a composite aqueous solution of chitosan oligosaccharide and sodium citrate, wherein the mass percentage of chitosan oligosaccharide and the mass percentage of sodium citrate is 4%, the mass percentage of sodium citrate is 0.2%, and the solvent is water; the calcium hydroxide suspension is kept at a constant temperature of 90±5°C in a water bath; the calcium hydroxide suspension kept at 90±5°C is stirred at 60 r / min, and then the composite aqueous solution of chitosan oligosaccharide and sodium citrate is added to the calcium hydroxide suspension under stirring, and the volume ratio of the composite aqueous solution of chitosan oligosaccharide and sodium citrate added to the calcium hydroxide suspension is 10:3; and carbon dioxide gas is introduced at a speed of 0.5 m / s. 3 / h, after aeration reaction for 4h, aeration was stopped, the suspension was air-cooled to room temperature, the solid-liquid was separated, the solid phase was washed with deionized water, and dried to obtain calcium carbonate powder;
[0051] (3) The calcium carbonate powder is dispersed in ethanol to form an ethanol dispersion, wherein the solid-liquid mass ratio of the calcium carbonate powder dispersed in the ethanol is solid / liquid = 1:20; the ethanol dispersion is kept at a constant temperature of 65±5°C in a water bath, condensed and refluxed, and after the constant temperature is maintained, chlorogenic acid and dopamine hydrochloride are added to the ethanol dispersion, wherein the mass ratio of the added chlorogenic acid and dopamine hydrochloride to the calcium carbonate powder is chlorogenic acid: dopamine hydrochloride: calcium carbonate powder = 1:0.4:1; after the addition is completed, the mixture is stirred at a constant temperature of 60r / min for 6h, then air-cooled to room temperature, the solid-liquid is separated, and the solid phase is dried to obtain the modified nano-calcium carbonate of this comparative example.
[0052] Comparative Example 3
[0053] A comparative calcium carbonate modification method comprises the following steps:
[0054] (1) keeping the deionized water bath at a constant temperature of 80±5°C, then adding calcium oxide powder to the deionized water, the mass ratio of calcium oxide powder to deionized water being 1:5; stirring at 100 r / min for 2 h after the addition, then standing at 80±5°C for 15 h to obtain a suspension of calcium hydroxide;
[0055] (2) preparing a composite aqueous solution of chitosan oligosaccharide and sodium citrate, wherein the mass percentage of chitosan oligosaccharide and the mass percentage of sodium citrate is 4%, the mass percentage of sodium citrate is 0.2%, and the solvent is water; the calcium hydroxide suspension is kept at a constant temperature of 90±5°C in a water bath; the calcium hydroxide suspension kept at 90±5°C is stirred at 60 r / min, and then the composite aqueous solution of chitosan oligosaccharide and sodium citrate is added to the calcium hydroxide suspension under stirring, and the volume ratio of the composite aqueous solution of chitosan oligosaccharide and sodium citrate added to the calcium hydroxide suspension is 10:3; and carbon dioxide gas is introduced at a speed of 0.5 m / s. 3 / h, after aeration reaction for 4h, aeration was stopped, the suspension was air-cooled to room temperature, the solid-liquid was separated, the solid phase was washed with deionized water, and dried to obtain calcium carbonate powder;
[0056] (3) dispersing the calcium carbonate powder in an ethanol solution of polyethylene glycol (PEG-1000) to obtain a dispersion, wherein the concentration of polyethylene glycol in the ethanol solution is 12 g / L, and the solid-liquid mass ratio of the calcium carbonate powder dispersed in the ethanol solution of polyethylene glycol is solid / liquid=1:30; dripping triethylamine into the dispersion, then the dispersion is thermostated to 70±5°C in a water bath, and after the thermostating, the dispersion is stirred at 60 r / min, and tridecafluorooctyl triethoxysilane is added to the dispersion during the stirring process. After the addition is completed, the stirring is continued at a constant temperature of 60 r / min for 3 hours, wherein the mass of the triethylamine added is 4 times the mass of the calcium carbonate powder in the dispersion; the mass of the tridecafluorooctyl triethoxysilane added is 2 times the mass of the calcium carbonate powder in the dispersion; then stopping the stirring, air cooling to room temperature, solid-liquid separation, and solid phase drying to obtain the modified nano calcium carbonate of this comparative example.
[0057] Example 5
[0058] The nano calcium carbonate prepared by the method described in the above embodiment or comparative example is added to the PE film, and the performance of the PE film is tested. The PE film is produced by weighing the following components by weight: 100 parts of polyethylene resin (weight average molecular weight 28000), 20 parts of nano calcium carbonate (respectively selected from the products prepared by the methods described in the above embodiments or comparative examples), 5 parts of polyurethane (weight average molecular weight 20000), 2 parts of dibutyltin maleate, and 5 parts of sodium stearate, and the above components are mixed evenly at 195°C, mixed for 40 minutes, and then extruded at 210°C, and the extruded material is hot-calendered at 180°C and a pressure of 20t; then the calendered film is biaxially stretched with a stretching ratio of 1.2, and after the stretching is completed, it is heat-set at 130°C for 5 minutes to obtain a PE film (all with a thickness of 60μm). The tensile strength of the PE film containing calcium carbonate prepared in the above embodiments or comparative examples was tested according to the method described in national standard GB / T 1040.3-2006, and the results are shown in Table 1. The high temperature and high humidity aging performance of the PE film containing calcium carbonate prepared in the above embodiments or comparative examples was tested according to the method described in national standard GB / T2423.3-2016, wherein the test temperature in the test box was 85±2°C, the humidity was 85%±2%, each group of PE films was cut into 100mm×100mm specimens, placed in the test box, and the appearance of the film surface was observed and recorded once every 100h until the PE film showed edge shrinkage and bulging, which was the detection end point. The results are shown in Table 1.
[0059] Table 1
[0060] Experimental Group Tensile strength(MPa) High temperature and high humidity aging time / h Example 1 22.6 2700 Example 2 23.1 2800 Example 3 22.9 2700 Example 4 22.8 2700 Comparative Example 1 19.1 2100 Comparative Example 2 18.3 1500 Comparative Example 3 18.7 1600
[0061] As can be seen from Table 1, after the modified nano calcium carbonate prepared by the method of the present invention is added to the PE film, the mechanical properties and high temperature and high humidity resistance of the PE film can be significantly improved. This is mainly because the modified nano calcium carbonate has good dispersion performance in the PE matrix, and the surface state of the modified calcium carbonate particles is optimized. The particles and the PE matrix have strong infiltration and bonding, and it is not easy to produce defects such as microcracks, so the mechanical and weather resistance are improved.
[0062] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for modifying nano calcium carbonate, characterized in that: The steps include: (1) Keep the deionized water bath at a constant temperature of 80±5°C, then add calcium oxide powder to the deionized water, stir for more than 2 hours after the addition is completed, and then stand at 80±5°C for more than 15 hours to obtain a suspension of calcium hydroxide; (2) preparing a composite aqueous solution of chitosan oligosaccharide and sodium citrate, and keeping the calcium hydroxide suspension in a water bath at a constant temperature of 90±5° C.; stirring the calcium hydroxide suspension kept at 90±5° C., and then adding the composite aqueous solution of chitosan oligosaccharide and sodium citrate to the calcium hydroxide suspension under stirring, while introducing carbon dioxide gas, and after aeration reaction for more than 4 hours, stopping aeration, air-cooling the suspension to room temperature, separating the solid and liquid, washing the solid phase with deionized water, and drying to obtain calcium carbonate powder; (3) dispersing the calcium carbonate powder in an ethanol solution of polyethylene glycol to obtain a dispersion, dropping triethylamine into the dispersion, and then thermostating the dispersion in a water bath to 70±5° C., stirring the dispersion after thermostatting, adding tridecafluorooctyl triethoxysilane to the dispersion during stirring, and continuing to thermostat stir for more than 3 hours after the addition is completed, then stopping stirring, air cooling to room temperature, separating the solid and liquid, and drying the solid phase to obtain a solid phase A; (4) The solid phase A is dispersed in ethanol to form an ethanol dispersion, the ethanol dispersion is kept at a constant temperature of 65±5° C. in a water bath, condensed and refluxed, and chlorogenic acid and dopamine hydrochloride are added to the ethanol dispersion after the constant temperature is maintained. After the addition is completed, the mixture is stirred at a constant temperature for more than 6 hours, and then air-cooled to room temperature, the solid-liquid separation is performed, and the solid phase is dried to obtain the modified nano-calcium carbonate.
2. A method for modifying nano calcium carbonate according to claim 1, characterized in that, The mass ratio of adding calcium oxide powder to deionized water is calcium oxide powder: deionized water = 1:5-6.
3. A method for modifying nano calcium carbonate according to claim 1, characterized in that, In the composite aqueous solution of chitosan oligosaccharide and sodium citrate, the mass percentage of chitosan oligosaccharide is 3% to 5%, the mass percentage of sodium citrate is 0.2% to 0.3%, and the solvent is water; the composite aqueous solution of chitosan oligosaccharide and sodium citrate is added to the suspension of calcium hydroxide in a volume ratio of calcium hydroxide suspension: composite aqueous solution of chitosan oligosaccharide and sodium citrate = 10:2 to 4.
4. A method for modifying nano calcium carbonate according to claim 1, characterized in that, The carbon dioxide gas introduction speed is 0.5m 3 / h.
5. A method for modifying nano calcium carbonate according to claim 1, characterized in that, In the polyethylene glycol ethanol solution, the concentration of polyethylene glycol is 10-15 g / L, and the solid-liquid mass ratio of the calcium carbonate powder dispersed in the polyethylene glycol ethanol solution is solid / liquid=1:
30.
6. A method for modifying nano calcium carbonate according to claim 1, characterized in that, The mass of the triethylamine added is 3 to 5 times the mass of the calcium carbonate powder in the dispersion; the mass of the tridecafluorooctyltriethoxysilane added is 1 to 2 times the mass of the calcium carbonate powder in the dispersion.
7. A method for modifying nano calcium carbonate according to claim 1, characterized in that, The solid-liquid mass ratio of the solid phase A dispersed in ethanol is solid / liquid=1:20; the mass ratio of the added mass of the chlorogenic acid and dopamine hydrochloride to the solid phase A is chlorogenic acid: dopamine hydrochloride: solid phase A=1-2:0.3-0.6:
1.
8. A PE film, characterized in that: The PE film contains the modified nano calcium carbonate obtained by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for preparing chlorogenic acid in Eucommia ulmoides leaves
CN102040519A
Method for surface modification on carbon fibers
CN103572591A